2017
DOI: 10.3390/molecules22081341
|View full text |Cite
|
Sign up to set email alerts
|

A Pectic Polysaccharide from Sijunzi Decoction Promotes the Antioxidant Defenses of SW480 Cells

Abstract: Sijunzi Decoction (SJZD) is a formula used for the treatment of spleen deficiency and gastrointestinal diseases in Traditional Chinese Medicine. Polysaccharides are reported to be the main components of SJZD responsible for its bio-functions. However, highly purified and clearly characterized polysaccharides from SJZD are not well described. Here we obtained a purified polysaccharide (SJZDP-II-I) from SJZD using ion exchange chromatography and gel filtration. Structure analysis by FT-IR and NMR identified SJZD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…JPYW is a TCM formula that is mainly composed of 8 ingredients: Panax ginseng C. A. Mey , Radix Paeoniae Alba , Codonopsis Radix , Poria cocos , Rhizoma Atractylodis Macrocephalae , Crataegus pinnatifida , Pericarpium Citri Reticulatae , and Cinnamomum cassia Presl . In TCM theory, JPYW is based on the Sijunzi decoction, which is a classic Chinese medicine that has been demonstrated to be beneficial for the spleen and stomach as a result of its antiaging effects [19, 21]. In a previous study, a JPYW capsule was proven to have therapeutic effects on gastric precancerous lesions and cancer-related fatigue [22].…”
Section: Introductionmentioning
confidence: 99%
“…JPYW is a TCM formula that is mainly composed of 8 ingredients: Panax ginseng C. A. Mey , Radix Paeoniae Alba , Codonopsis Radix , Poria cocos , Rhizoma Atractylodis Macrocephalae , Crataegus pinnatifida , Pericarpium Citri Reticulatae , and Cinnamomum cassia Presl . In TCM theory, JPYW is based on the Sijunzi decoction, which is a classic Chinese medicine that has been demonstrated to be beneficial for the spleen and stomach as a result of its antiaging effects [19, 21]. In a previous study, a JPYW capsule was proven to have therapeutic effects on gastric precancerous lesions and cancer-related fatigue [22].…”
Section: Introductionmentioning
confidence: 99%
“…RNA extraction from the intestine cells and real-time PCR for antioxidant gene detection were performed as previously reported ( 17 ). In summary, IPEC-J2 cells were lysed with Trizol Regent (R1100, Beijing Solarbio Science & Technology Co., Ltd., China), and the total RNA was extracted from the cells according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…9 The pectin polysaccharide in SJZD can also promote the antioxidant defense of SW480 cells. 10 So far, no studies have found SJZD in the treatment of skin diseases, including vitiligo. Exploring the potential therapeutic effect of SJZD on non-segmental vitiligo is not only conducive to deepening the understanding of the medicinal value of SJZD, but also pioneering new therapeutic drugs for the treatment of vitiligo.…”
Section: Introductionmentioning
confidence: 99%